2019
DOI: 10.1101/534990
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Monkey EEG links neuronal color and motion information across species and scales

Abstract: It remains challenging to relate EEG and MEG to underlying circuit processes and comparable experiments on both spatial scales are rare. To close this gap between invasive and noninvasive electrophysiology we developed and recorded human-comparable EEG in macaque monkeys during visual stimulation with colored dynamic random dot patterns. Furthermore, we performed simultaneous microelectrode recordings from 6 areas of macaque cortex and human MEG. Motion direction and color information were accessible in all si… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…Here we explore a new approach to address the neural mechanisms for encoding hue and luminance contrast, using magnetoencephalography (MEG) in humans, coupled with multivariate analysis [44][45][46][47][48] (Figure 1). Color can be decoded from MEG activity [49][50][51][52][53][54][55][56] . In the present work, we exploit the exquisite temporal resolution of MEG to tease apart the neural mechanisms for hue and luminance contrast.…”
mentioning
confidence: 99%
“…Here we explore a new approach to address the neural mechanisms for encoding hue and luminance contrast, using magnetoencephalography (MEG) in humans, coupled with multivariate analysis [44][45][46][47][48] (Figure 1). Color can be decoded from MEG activity [49][50][51][52][53][54][55][56] . In the present work, we exploit the exquisite temporal resolution of MEG to tease apart the neural mechanisms for hue and luminance contrast.…”
mentioning
confidence: 99%
“…The color percept associated with a stimulus can be decoded from functional magnetic resonance imaging activity [10], MEG and EEG in humans and monkeys [11][12][13][14], or responses of single neurons in monkeys [15,16]. Moreover, as many of these studies show, the extent to which activity patterns reflect the sequence of hues in the color wheel can be used to identify neurons and brain areas that are likely involved in encoding color.…”
mentioning
confidence: 99%
“…It is a challenge to directly compare invasive (single‐unit) recordings to MEG for a number of reasons: (a) the specific cellular and circuitry mechanisms that contribute to MEG signals is still unknown (Cohen, ); (b) macroscale signals from MEG suffer an ill‐posed inverse problem when attempting to deduce microscale properties. A recent study bridged the gap between invasive and noninvasive recordings in a different visual task (Sandhaeger, von Nicolai, Miller, & Siegel, ) and found that tuning of the two signals were similar in the extrastriata visual cortex (V4), but not in frontal areas (Sandhaeger et al, ), demonstrating that more work needs to be done to link invasive and noninvasive measures. Here, all the PEF and FEF peaks occurred prior to mean antisaccade movements for fast (213 ± 20ms) and slow (263 ± 30ms) trials.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study bridged the gap between invasive and noninvasive recordings in a different visual task (Sandhaeger, von Nicolai, Miller, & Siegel, 2019) and found that tuning of the two signals were similar in the extrastriata visual cortex (V4), but not in frontal areas (Sandhaeger et al, prior to mean antisaccade movements for fast (213 ± 20ms) and slow (263 ± 30ms) trials. A limitation for most of the previous studies is that measurements were done on either PEF or FEF alone (monkey single-unit recording (Bisley et al, 2004;Everling, Dorris, & Munoz, 1998;Schmolesky et al, 1998;Thompson et al, 1996).…”
Section: Saccade-preparation (Stimulus-aligned)mentioning
confidence: 99%